1980
DOI: 10.1128/aac.18.6.877
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella species: antimicrobial susceptibilities, bactericidal kinetics, and in vitro inactivation of beta-lactam agents

Abstract: In vitro properties of 19 antimicrobial agents were tested with 56 isolates of Klebsiella spp. The aminoglycosides and the new beta-lactam compounds cefotaxime and moxalactam were the most inhibitory drugs tested. Chloramphenicol, tetracycline, trimethoprim, and trimethoprim-sulfamethoxazole were moderately active, whereas piperacillin, mezlocillin, and furazlocillin were ineffective against 25% of the isolates. Gentamicin was the only agent tested that was uniformly bactericidal in time-kill experiments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Until recently, a relatively small number of cases of Klebsiella oxytoca bacteremia were included in previous studies of Klebsiella bacteremia [3,4,5,6,7,8]. However, previous investigators found no significant differences between the clinical features of Klebsiella pneumoniae bacteremia and those of Klebsiella oxytoca bacteremia [4,20]. To our knowledge, this is the largest series of Klebsiella oxytoca bacteremia.…”
Section: Discussionmentioning
confidence: 82%
“…Until recently, a relatively small number of cases of Klebsiella oxytoca bacteremia were included in previous studies of Klebsiella bacteremia [3,4,5,6,7,8]. However, previous investigators found no significant differences between the clinical features of Klebsiella pneumoniae bacteremia and those of Klebsiella oxytoca bacteremia [4,20]. To our knowledge, this is the largest series of Klebsiella oxytoca bacteremia.…”
Section: Discussionmentioning
confidence: 82%
“…Infections caused by KO are nearly always nonarticular and predominately occur in the nosocomial setting in patients with concurrent medical conditions [13][14][15][16][17][18]. Similarly, the likelihood of a GBS infection is increased in individuals who are immunocompromised because of underlying conditions such as diabetes [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Panwalker and his associates [9] have shown that moxalactam does not •' Number of strains tested. l'M !C,ll(pg/ml). '…”
Section: Discussionmentioning
confidence: 99%